I'm a Little Teapot - Trapani, Iza (Danvers, MA, 1996)
Expanded verses of a familiar song tell how a teapot dreams of visiting China, Mexico, the opera, a jungle, and other places while waiting to be used to serve tea.
Easy
Keywords: Children's songs; Texts